Financial capital and social capital: two ingredients of development (Revista LIDER, 2021)
The term ´development´ has generated a lot of controversies and mistrust, but it has also been a source of valuable discussions, which guide policy developers in conceptualization and execution of public policies to achieve a better quality of life, in an acceptable social and economic model with respect to ecological rules. This work approaches the relation that exists between the concepts of development and sustainability through two fundamental terms or areas: social capital and financial capital. While the first one deals with norms and rules, written or tacit, that maintains a cohesive society, the second deals with the sources and uses of financial resources that support or limit development policies. The positive or negative existence of synergy between these two kinds of capital can determine, in the short run as well as in the long term, the real possibility that a society has of reaching better status, in terms of socioeconomic development.